Comparative Evaluation of Infraorbital Nerve Recovery Following Open and Closed Reduction of Zygomatic Complex Fracture - Dua Fatima Kolachi Baloch, Muhammad Shahzad, Lovekesh Kumar, Syed Zafar Abbas, Naeem Mustafa, Salman Shams, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the recovery of infraorbital nerve injury following zygomatic complex fracture management with open reduction and close reduction. Material and Methods: A sum of 128 subjects with zygomatic complex break and infraorbital nerve damage were incorporated in the research, and they were evenly divided into two collection: Close (Group A) and Open (Group B). A neurosensory assessment was carried out. The front cheek, lateral side of the nose, and upper lip were all inspected bilaterally. If two consecutive positive answers were obtained after 24 weeks, the result was referred to as recovery. The researchers used descriptive statistics. Results: The mean fracture duration in group A was 20.31±9.45 hours, whereas it was 20.65±9.16 hours in group B. In comparison to Group A, Group B had superior results at the end of 24 weeks. Infraorbital nerve damage restoration was found to be 34.3 % in group A and 64.06 % in group B. Conclusion: When contrasted to closed reduction, the probability of recoveries is higher with open reduction. Keywords: